The first recognized mafic-siliciclastic VMS deposit in middle Eocene back-arc rift setting, Sey Deresi, Southeastern Anatolian Orogenic Belt, Türkiye - Yildirim, Nail; Donmez, Cahit; Hanilci, Nurullah; Yildirim, Esra; Ozbas, Fatih; Sonmez, Yunus; Banks, David (Pergamon-Elsevier Science Ltd, 2026)
This study investigates the geological, geochemical and mineralogical characteristics of the Sey Deresi mineralization hosted within Middle Eocene volcanic and sedimentary rocks in the Southeastern Anatolian Orogenic Belt in T & uuml;rkiye. The main aim of this study is to constrain the genetic type of the deposit and to evaluate its metallogenic significance within the regional geodynamic framework. The mineralization occurs as massive, semi-massive, and disseminated ore bodies spatially associated with tholeiitic basalt and tuffaceous siliciclastic rocks deposited in a continental back-arc setting during a period of rapid basin deepening. The ore assemblage is dominated by pyrite, accompanied by chalcopyrite, sphalerite, and bornite. The host rocks are characterized by pervasive chlorite, sericite, carbonate, and silica alteration assemblages. Fluid inclusions yield homogenization temperatures mostly between 250 and 310 degrees C and salinities of 5 to 10 wt% NaCl equivalent. Sulfur isotope values of pyrite range from +2 to +6 parts per thousand, suggesting a mixed sulfur origin derived from mafic volcanic sources and thermochemically reduced seawater sulfate. Primitive mantle-normalized metal patterns display marked enrichments and closely resemble those characteristics of Besshi and/or pelitic-mafic deposits. These characteristics suggest that the Sey Deresi Cu-Zn mineralization formed as a VMS system associated with mafic volcanic and siliciclastic rocks in a continental back-arc rift setting. As the first documented example of this deposit type within the Southeastern Anatolian Orogenic Belt, this mineralization provides new insights into the tectonomagmatic evolution of the region and highlights the previously underrecognized VMS exploration potential of southeastern T & uuml;rkiye.
Keywords: Mafic-Siliciclastic Vms; Southeastern Anatolian Orogenic Belt; Middle Eocene; Sulfur Isotopes; Trace Element Geochemistry; Fluid Inclusions